A rational sine and cosine of the angles of a triangle - Mazėtis, Edmundas; Melničenko, Grigorijus (Lietuvos matematikos rinkinys, 2013)
The article deals with triangles whose sines and cosines of the angles are the rational numbers. We prove that these triangles are similar to Pythagorean or Heronian triangles, and vice versa.
Keywords: Pythagorean triangles; Heronian triangles; Pythagorean angles; sines; cosines